Curriculum Reforms and Physical Education: the Theoretical-Conceptual knowledge of the Spanish School Population - Hernández Álvarez, Juan Luis; Velázquez Buendía, Roberto; Martínez Gorroño, Eugenia (Education Policy Analysis Archives, 2007)
This article analyses the changes generated by the implementation of a new curriculum in the context of the new Law of Education in Spain. In that context, our interest is centered in the reflection about the influence of educational policies in the development of Physical Education as a subject matter. We use a historical perspective to analyze some of the changes introduced by the Ley de Ordenación General del Sistema Educativo Español (LOGSE, 1990), and the curricular reform. In particular, we base our analysis on the introduction of the theoretical-conceptual contents (“to know”) in the curricular area of Physical Education, which has traditionally centered in the “know how”. In order to carry out our analysis, we took as a point of departure the results obtained from the research on what the Spanish school population knows about the theoretical-conceptual contents. The focus of the investigation was the Spanish school population between the ages of 10 and 16. A Questionnaire on the Learning of Concepts in PE was applied to a representative sample (n=2,721) of the said school population. Results show that, in general, the students of both primary and secondary education have a poor theoretical and conceptual knowledge, reaching worrying proportions in some cases. The results also show the need to develop strategies that lead the improvement of the “PE culture” among students of both primary and secondary education. The learning of these contents is a fundamental factor in the education of autonomous citizens, committed to caring for their bodies and their health, and thus achieving a good quality of life. The study shows that the curricular reform by itself is insufficient to introduce new contents. Thus it is also necessary to implement measures of support to teachers so that the proposed changes become a reality.